Akupresur dan Perubahan Keluhan ISPA pada Pasien Balita - I Wayan Suardana; Ni Luh Kompyang Sulisnadewi; Laksmyta Adil; Anak Agung Ngurah Taruma Wijaya (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2016)
The purpose of this study was to determine the effect of the acupressure therapy to changing patient ARI sickness in infants in Holistic Nursing Care Latu Usadha Abiansemal Badung. This study used quasy experiment with using a pretest-posttest control group design. The sample consisted of 30 people, 15 people for the treatment group and 15 to the control group. The collection of data by using the form. Observation overview of signs and symptoms of respiratory infection. The average score of pre-test was 4.06, post-test was 3.86 in the control group and an average score of pre-test was 4.13, post-test was 2.06 in the treatment group. Data were analyzed using the Wilcoxon signed rank test and the Mann Whitney test. Results of p = 0.000 (p 0.05), which means that Ho refused. This meant that acupressure was effective in changing the ARI sickness in patients under five years old in Holistic Nursing Care Latu Usadha Abiansemal Badung